The impact of foreign board membership on firm value - Oxelheim, Lars; Randøy, Trond (Journal of Banking & Finance, 2003)
This study examines the effect of foreign (Anglo-American) board membership on corporate performance measured in terms of firm value (Tobin’s Q). Using a sample of firms with headquarters in Norway or Sweden the study indicates a significantly higher value for firms that have outsider Anglo-American board member(s), after a variety of firm-specific and corporate governance related factors have been controlled for. We argue that this superior performance reflects the fact that these companies have successfully broken away from a partly segmented domestic capital market by “importing” an Anglo-American corporate governance system. Such an “import” signals a willingness on the part of the firm to expose itself to improved corporate governance and enhances its reputation in the financial market.